Investigation of Web Post Compression Buckling Limit State and Stiffener Requirements in Castellated Beams - Menkulasi, Fatmir; Moen, Christopher D.; Eatherton, Matthew R.; Kuruppuarachchi, Dinesha (Engineering Journal, 2017)
The research presented in this paper addresses the need for a design method to estimate the nominal capacity of castellated beams against concentrated loads. The limit state investigated is that of web post buckling due to compression loads. The purpose of the paper is twofold: (1) to investigate the limit state of web post buckling due to compression loads and (2) to quantify the enhanced capacity of the web post against concentrated loads when stiffeners are provided. Five castellated beam depths are considered, which cover a wide range of the available depths. For each beam section, three load cases are investigated: (1) center of load aligns with the middle of web post, (2) center of load aligns with the center of the hole, and (3) center of load aligns with a point half-way between the center of web post and center of hole. For each load position, two cases are considered: one without a stiffener and one with full-height transverse stiffeners. Each case is investigated using nonlinear finite element analysis to examine the behavior of the web post to failure. The efficiency of stiffeners to increase the resistance of castellated beams against concentrated loads is examined. For each investigated beam depth and stiffener arrangement, the loads that cause failure are noted. In addition, a simplified approach for checking the limit state of web post buckling in compression is proposed.